Hot Weather Exposure and Human Health in Vietnam: Impacts, Risk Distribution, and Adaptation Strategies - Nguyen Thi Thu Thuy; Dao Nguyen Manh; Quach Thi Quynh; Pham Thi Phuong Lien; Tran Thanh Tuan; Chu Duc Thanh; Do Thi Thuy Trang; Trinh Quang Minh; Vu Thi Loan; Nguyen Van Thanh (Environmental Research and Planetary Health, 2026)
In the context of climate change, extreme heat in Vietnam has been increasing markedly in frequency, intensity, and duration, becoming one of the leading environmental threats to public health. This study aims to synthesize scientific evidence on the impacts of heat on human health, analyze the current situation and risk distribution in Vietnam, and propose appropriate response measures. Heat not only directly affects health but also has far-reaching impacts on labor productivity and socio-economic development. Evidence from Vietnam indicates that heat is associated with an increase in physiological and pathological disorders such as dehydration, electrolyte imbalance, cardiovascular and respiratory diseases, kidney injury, and mental health disorders. Prolonged heatwaves increase the risk of hospitalization and mortality, particularly among vulnerable groups such as the elderly, children, pregnant women, individuals with chronic diseases, and outdoor workers. The distribution of risk is uneven, with higher concentrations in major urban areas and the southern region due to prolonged high temperatures combined with high humidity and the urban heat island effect; the North Central and Central Coastal regions are also severely affected due to hot, dry winds. Notably, heat exposure has resulted in the loss of 16 billion working hours annually, leading to economic losses of approximately USD 23 billion (as of 2022). In response to this situation, priority should be given to adaptation measures suited to Vietnam’s context, including raising public awareness, protecting vulnerable populations, adjusting working conditions, improving living environments, and promoting effective cooling solutions. These directions are crucial for mitigating the health impacts of heat in the future.